EVEREST study report 2: imaging and grading protocol, and baseline characteristics of a randomised controlled trial of polypoidal choroidal vasculopathy. Issue 5 (10th March 2015) - Tan, Colin S; Ngo, Wei Kiong; Chen, Jian Ping; Tan, Nikolle W; Lim, Tock Han; ,
Abstract : Purpose: To describe the imaging standards, grading protocol and baseline characteristics of polypoidal choroidal vasculopathy (PCV) from the EVEREST study. Methods: In a prospective, multicentre study, confocal scanning laser ophthalmoscope indocyanine green angiography (ICGA) was performed using a standardised imaging protocol. All images were graded using standardised, calibrated equipment by fellowship-trained ophthalmologists at the Central Reading Center. Results: Sixty-one patients with PCV were included in the study. ICGA characteristics included: nodular appearance stereoscopically (56 eyes, 91.8%), hypofluorescent halo (42, 68.9%), abnormal vascular network (54, 88.5%) and pulsation of the polyps (4, 6.6%). Colour fundus photography revealed orange subretinal nodules (34, 55.7%) and massive submacular haemorrhage (8, 13.1%). The mean area of the PCV lesion was 3.11 mm 2 (range, 0.2–10.7 mm 2 ). The vascular channels filled within 7.3–32.0 s (mean: 17.9 s) while the mean filling time for polyps was 21.9 s (range, 7.3–40.4 s). Patients with massive submacular haemorrhage were less likely to have abnormal vascular channels seen on ICGA (28.6% vs 83.3% for those without massive haemorrhage, p=0.001). Conclusions: The imaging and grading protocols and baseline characteristics of a multicentre, randomised controlled trial of PCV are described in detail, and may serve as reference for future randomised, controlled trials on PCV. Clinical trial number: This work was supported by Novartis Pharma AG, Basel, Switzerland grant number NCT00674323 (clinicaltrials.gov).